The Influence of the Type of Educational Environment on Preschool Children's Mental Development - Shishova E.O. (Психолого-педагогические исследования, 2021)
The article is devoted to the study of the developing potential of educational environments and their impact on the formation of personality in the modern educational space. Based on the theoretical and methodological analysis of the types of educational environment, it is concluded that in the structural plan the educational environment of preschool childhood is a system of interconnected components, the main components include object-spatial, socio-psychological, cognitive-active, communicative and subjective components. Based on cluster analysis, four distinctive modern types of educational environment with various capabilities are identified and the author's typology of educational environments in the system of preschool education is proposed, depending on the severity of each component. The tendencies to the conjugation of the quality parameters of the educational environment (according to the ECERS-R scales) and the personal characteristics of children, as well as significant differences in the subjective characteristics and initiative of preschoolers in different learning environments have been identified. The efficiency and feasibility of using the cluster analysis method in the study of the qualitative characteristics of the educational environment and their developing potential is shown. Empirical data were obtained on the basis of 16 preschool educational organizations in the Republic of Tatarstan, on a sample of subjects in 876 people (50 teachers, 413 preschool children and 413 parents (mothers) of preschool children).